Lithium manganese iron phosphate positive electrode material and preparation method thereof
By employing a core-shell structure design with a large manganese-rich core and an iron-rich outer shell, and a spray drying process, the problems of manganese dissolution and structural stability in lithium manganese iron phosphate materials have been solved, resulting in improved high density and long-cycle performance, making them suitable for large-scale industrialization.
Patent Information
- Application Number
- CN202511074607.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-01
- Publication Date
- 2025-11-07
AI Technical Summary
Existing lithium manganese iron phosphate materials suffer from structural collapse problems caused by manganese dissolution and the Jahn-Teller effect, resulting in poor capacity retention and low compaction density. Existing coating methods are complex and difficult to industrialize on a large scale.
The core-shell structure design employs a large-particle manganese-rich core and an iron-rich outer shell. The particle size distribution is formed through spray drying and thermal decomposition processes. The manganese-rich core provides a high voltage platform, while the iron-rich outer shell reduces manganese dissolution. Combined with a suitable molar ratio difference between the inner and outer layers, lattice mismatch is reduced.
It improves the compaction density and cycle performance of lithium manganese iron phosphate, simplifies the preparation process, and achieves high energy density and long cycle stability, making it suitable for large-scale production.
Smart Images

Figure CN120914229A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a lithium ion battery cathode material, in particular to a lithium manganese iron phosphate material with size grading of particles, and large particles with an internal manganese-rich core and an external iron-rich shell, and a preparation method thereof. BACKGROUND
[0002] Lithium ion batteries use material reversible Faraday reaction to realize energy storage and conversion, have long cycle life, no memory effect, high specific energy, environmental friendly and other advantages, are widely used in electrochemical energy storage devices. The cathode material of lithium ion battery is an important part of lithium ion battery, and plays a decisive role in the performance of lithium ion battery. Olivine lithium iron phosphate (LiFePO4) has the advantages of high safety, high temperature resistance, overcharge resistance, long cycle life and low cost, so it has good prospects for application in power battery, and is one of the lithium ion battery cathode materials successfully realized commercial application. However, due to its low specific capacity (170mAhg -1 ) and working voltage (3.45V vs. Li / Li + ), the energy density of LiFePO4 battery is difficult to be further improved. In order to improve the energy density of LiFePO4 battery, a proper amount of manganese is doped into lithium iron phosphate material, so that the lithium manganese iron phosphate (LiMn x Fe 1- x PO4) with high discharge platform and good low temperature working performance is born. LiMn x Fe 1-x PO4 has similar olivine structure with LiFePO4, and its working voltage reaches 4.10V, and the energy density is increased by about 20% compared with that of LiFePO4. Although the energy density of lithium manganese iron phosphate is improved, manganese will dissolve in the cycle process, which makes the capacity retention rate worse, and Jahn-Teller effect will also occur, which makes the crystal produce deformation, leading to structure collapse, which induces manganese to dissolve in electrolyte, making the capacity retention rate worse. In addition, due to the characteristics of insulator, the conductivity of lithium manganese iron phosphate is low, which makes it difficult for lithium ion to escape from the crystal, showing low capacity. The industry often reduces the primary particle size to shorten the diffusion distance of lithium ion to avoid this problem, but also leads to the low practical tap density of lithium manganese iron phosphate (2.3g / cm 3 ), which is far less than the commercial tap density of lithium iron phosphate (2.6g / cm 3). Low compaction and manganese dissolution are the two key factors that limit the commercialization of lithium manganese iron phosphate. Coating lithium iron phosphate with the same structure on the surface of lithium manganese iron phosphate to prepare core-shell structure is a more effective means. The outer layer of lithium iron phosphate acts as a barrier between the lithium manganese iron phosphate phase and the electrolyte, preventing direct contact and reducing manganese dissolution caused by electrolyte corrosion. In addition, lithium iron phosphate itself also provides capacity as an effective active ingredient, but existing methods have poor coating effect, complex preparation process and difficulty in large-scale industrialization. At the same time, it cannot improve the compaction density of the material. For example: the invention patent with publication number CN120089701A provides a method for preparing a core-shell structure lithium manganese iron phosphate cathode material by quenching heat treatment. The coating structure is formed on the surface of lithium manganese iron phosphate, reducing the reaction between manganese and electrolyte, inhibiting the dissolution of manganese, alleviating the ginger effect of manganese, and improving the stability of the material. However, the preparation process is complex, and the quenching process has high risk, making it difficult to mass-produce. Invention patent CN 105990562B provides a method for preparing nano lithium manganese iron phosphate composite material and its preparation method. The obtained lithium manganese iron phosphate-based positive electrode material has high discharge capacity, good rate performance and cycle performance, but the synthesized nano-particle lithium manganese iron phosphate product has low compaction density. Therefore, the core-shell structure is prepared by coating carbon, nitride, iron compound, etc. to improve its performance, but the preparation process is complex, and the compaction performance and cycle performance of the material are limited, which restricts its application. SUMMARY
[0003] The purpose of the present application is to improve the compaction performance and cycle performance of lithium manganese iron phosphate, and to provide a lithium manganese iron phosphate cathode material with high compaction and long cycle. Another purpose of the present application is to provide a preparation method of the above-mentioned material.
[0004] The technical scheme of the present application is as follows: a lithium manganese iron phosphate cathode material, comprising a large-particle core-shell structure lithium manganese iron phosphate and a small-particle lithium manganese iron phosphate; the large-particle core-shell structure lithium manganese iron phosphate comprises a manganese-rich lithium manganese iron phosphate core and an iron-rich lithium manganese iron phosphate shell, and the content of manganese in the core is greater than that in the shell, and the content of iron in the core is less than that in the shell.
[0005] The present application also provides a preparation method of the above-mentioned lithium manganese iron phosphate cathode material, comprising the following steps:
[0006] (1) Preparation of manganese-rich lithium manganese iron phosphate slurry: mix and grind manganese-rich lithium manganese iron phosphate with water to obtain manganese-rich lithium manganese iron phosphate slurry;
[0007] (2) Preparation of iron-rich lithium manganese iron phosphate slurry: dissolve a thermal decomposition type water-soluble manganese source and an iron source in water, then add a non-water-soluble lithium source, a phosphorus source, and mix and grind with water to obtain an iron-rich lithium manganese iron phosphate slurry;
[0008] (3) mixing the iron-rich lithium manganese iron phosphate slurry obtained in step (2) and the manganese-rich lithium manganese iron phosphate slurry obtained in step (1) with a carbon source to obtain a precursor slurry;
[0009] (4) spray drying and thermal decomposition: spray drying the precursor slurry to obtain a precursor;
[0010] (5) heating and calcining the precursor obtained in step (4) under a protective atmosphere, and obtaining a lithium manganese iron phosphate positive electrode material after cooling.
[0011] Further, in the manganese-rich lithium manganese iron phosphate in step (1), the molar ratio of manganese to iron is n(Mn) / n(Fe) = 1-4, preferably n(Mn) / n(Fe) = 1.25-2.5. In step (2), the molar ratio of the manganese source to the iron source is n(Mn) / n(Fe) = 0.25-0.67. The core manganese-rich lithium manganese iron phosphate Mn / Fe ≥ 1 guarantees high voltage of the material, while Mn / Fe ≤ 4 avoids the dilemma of poor conductivity and inability to exert capacity due to excessive manganese content, achieving a good balance in energy release at the material design end. The shell layer establishes a barrier between the core and the electrolyte, directly contacting the electrolyte, and the low-manganese high-iron design of the shell layer Mn / Fe ≤ 0.67 can better reduce the harm caused by manganese dissolution due to Jahn-Teller; and by reducing the difference in manganese and iron composition between the core layer and the shell layer through the design of the shell layer Mn / Fe ≥ 0.25, the phenomenon of lattice mismatch caused by composition mutation can be alleviated.
[0012] Further, in step (2), the thermal decomposition type water-soluble manganese source is one or more of manganese nitrate, manganese acetate, manganese citrate, manganese tartrate, and manganese ammonium sulfate; the thermal decomposition type water-soluble iron source is one or more of iron nitrate, iron acetate, iron tartrate, ferrous ammonium sulfate, ferric ammonium citrate, and ferrous oxalate; and the carbon source in step (3) is one or more of glucose, sucrose, starch, cellulose, polyvinyl alcohol, soluble starch, cellulose, ascorbic acid, or phenolic resin.
[0013] Further, in step (3), the manganese-rich lithium manganese iron phosphate slurry and the iron-rich lithium manganese iron phosphate slurry are mixed in a mass ratio of manganese-rich lithium manganese iron phosphate to theoretically generated iron-rich lithium manganese iron phosphate equal to 5-9:1-5. The mass ratio of manganese-rich slurry to iron-rich slurry will affect the thickness and grading effect of the coating layer, so it has more excellent performance in long cycle and manganese dissolution protection, and increasing the proportion of iron-rich slurry will increase the proportion of small particles, which will be beneficial to the capacity; however, too high a proportion of iron-rich slurry will result in too high a proportion of small particles, leading to poor grading effect and reduced tap density.
[0014] Further, the amount of carbon source added is 8-15% of the total mass of the finished lithium manganese iron phosphate, preferably 12%.
[0015] Further, the particle size range of the manganese-rich lithium manganese iron phosphate slurry in step (1) is D50 = 0.3-1 um, and the particle size range of the iron-rich slurry in step (2) is D50 = 0.1-0.6 um. The particle size of the manganese-rich lithium manganese iron phosphate slurry in step (1) is greater than that of the iron-rich slurry in step (2), and too small particle size of the manganese-rich slurry or too large particle size of the iron-rich slurry will not form a size particle grading, and the compaction density cannot be improved; due to the low conductivity of lithium manganese iron phosphate, further increasing the particle size of the manganese-rich slurry will increase the difficulty of lithium ion diffusion, and the capacity is difficult to develop, so the particle size of the manganese-rich slurry should not be too large; small particles have the characteristics of spontaneous agglomeration, and when ordinary process is used to prepare size particle grading material, the particle size of the iron-rich slurry may cause small particles to be adhered and agglomerated, thereby being difficult to fill the voids of large particles, and the grading effect cannot be formed. The present application uses spray drying method combined with thermal decomposition type manganese source and iron source to inhibit particle agglomeration and excessive growth, and ensure the effectiveness of size particle grading.
[0016] Further, the inlet air temperature of the spray drying in step (4) is 180-320℃, and the outlet air temperature is 85-115℃.
[0017] In the secondary batching, thermal decomposition type water-soluble manganese source and iron source are used, and the liquid droplet microzone reaction of spray drying is used to limit the nucleation sites of the iron-rich lithium manganese iron phosphate. In the spray drying process, the solid manganese-rich precursor core and lithium source / phosphorus source are preferentially precipitated to form a sphere. Due to the surface tension, the liquid part of the thermal decomposition type water-soluble iron-rich slurry is precipitated and decomposed on the surface of the manganese-rich core solid particles by using the high temperature (200-300℃) in the spray drying process, so as to be adsorbed on the surface of the sphere. With the evaporation of water, the manganese source and iron source in the part of the iron-rich slurry are precipitated and coated on the surface of the manganese-rich precursor core, realizing the coating effect of manganese-rich core + iron-rich outer layer, and improving the structural stability of the material. The remaining manganese source and iron source in the iron-rich slurry are precipitated as small particles with mixed lithium source / phosphorus source as the second nucleation point, serving as the lithium iron phosphate precursor of the iron-rich type, and forming size particle grading with the core-shell lithium manganese iron phosphate, improving the particle density, and finally improving the compaction density of the finished product. After sintering, the manganese-rich lithium manganese iron phosphate coated with the iron-rich lithium manganese iron phosphate has a core-shell structure, and the large particles and the small particles of the iron-rich lithium manganese iron phosphate are filled with each other to form a size particle grading spherical lithium manganese iron phosphate, which improves the compaction density of the lithium manganese iron phosphate and the material stability in the long cycle process. At the same time, the thermal decomposition type manganese source and iron source produce gas during the heat treatment process, inhibit the excessive growth of particle agglomeration, form fine and uniform lithium manganese iron phosphate particles, and further promote the grading effect of size particles to further improve the compaction density.
[0018] The core-shell gradient structure: the high manganese content in the manganese-iron lithium phosphate in the inner core maintains a high voltage platform to improve the energy density, and the high iron content in the outer layer of the manganese-iron lithium phosphate reduces the probability of direct contact of the Mn phase with the electrolyte, reduces the manganese source dissolution caused by the Jahn-Teller effect, and improves the material stability. The design of the manganese-iron concentration difference of the core-shell reduces the molar ratio difference of the elements in the inner and outer layers, and reduces the lattice mismatch caused by the composition mutation.
[0019] Advantages: compared with the prior art, the present application has the following obvious advantages: 1. the inner core of the manganese-iron lithium phosphate in the core-shell structure maintains a high voltage platform to improve the energy density, and the outer layer of the manganese-iron lithium phosphate reduces the manganese dissolution caused by the Jahn-Teller effect, and improves the material stability; 2. the suitable molar ratio difference of the elements in the inner and outer layers reduces the lattice mismatch caused by the composition mutation; 3. the integrated process design is simple, and multiple steps such as drying, coating, thermal decomposition and particle self-assembly are completed in one step by the spray drying process; 4. the large particles with the core-shell structure and the small particles of the manganese-iron lithium phosphate are filled with each other to form a size grading spherical manganese-iron lithium phosphate, which improves the compaction density of the manganese-iron lithium phosphate and the material stability in the long cycle process; 5. the gas generated in the thermal decomposition process of the manganese source and the iron source inhibits the particle agglomeration, forms small and uniform manganese-iron lithium phosphate particles, and further improves the compaction density. BRIEF DESCRIPTION OF DRAWINGS
[0020] Figure 1 SEM image of Example 3 of the present application;
[0021] Figure 2 SEM image of Example 8 of the present application. DETAILED DESCRIPTION
[0022] The technical solutions of the present application will be further described below in combination with examples and drawings, and the reagents used are commercially available.
[0023] Example 1
[0024] The preparation method of the manganese-iron lithium phosphate cathode material provided by the present application comprises the following steps:
[0025] (1) preparing a manganese-rich manganese-iron lithium phosphate slurry: mixing manganese-rich manganese-iron lithium phosphate with pure water, sand milling to D50=0.4um, and obtaining a manganese-rich manganese-iron lithium phosphate slurry, wherein the molar ratio of manganese to iron is n(Mn) / n(Fe)=4;
[0026] (2) preparing a manganese-rich manganese-iron lithium phosphate slurry: adding manganese acetate, ferrous acetate, lithium carbonate and phosphoric acid to pure water according to Li / P=1.01, Mn / Fe=0.25, (Mn+Fe) / P=0.965, stirring and dispersing uniformly, sand milling to D50=0.2um, and discharging to obtain a manganese-rich manganese-iron lithium phosphate slurry;
[0027] (3) The manganese-rich lithium manganese iron phosphate slurry obtained in step (1) is mixed with the iron-rich lithium manganese iron phosphate slurry obtained in step (2) at a mass ratio of (manganese-rich lithium manganese iron phosphate: theoretically generated iron-rich lithium manganese iron phosphate = 6:4), 12% of the mass of the manganese-rich lithium manganese iron phosphate material is added to glucose, and the mixture is stirred uniformly to obtain a precursor solution;
[0028] (4) The precursor solution is subjected to spray drying to obtain a precursor, the inlet air temperature of the spray drying is 280 DEG C, and the outlet air temperature is 100 DEG C;
[0029] (5) The precursor is sent into a high-temperature furnace, calcined at 740 DEG C for 10 h under a nitrogen atmosphere, taken out after cooling, and a lithium manganese iron phosphate positive electrode material is obtained;
[0030] Example 2
[0031] The preparation method of the lithium manganese iron phosphate positive electrode material provided by the application comprises the following steps:
[0032] (1) A manganese-rich lithium manganese iron phosphate slurry is prepared: manganese-rich lithium manganese iron phosphate is mixed with pure water, sand grinding is performed until D50 = 0.6 um, and a manganese-rich lithium manganese iron phosphate slurry is obtained, wherein the molar ratio of manganese to iron is n(Mn) / n(Fe) = 2.33;
[0033] (2) An iron-rich lithium manganese iron phosphate slurry is prepared: manganese acetate, ferrous acetate, lithium carbonate and phosphoric acid are added to pure water according to Li / P = 1.01, Mn / Fe = 0.43 and (Mn+Fe) / P = 0.965, stirring and dispersion are performed until uniform, sand grinding is performed until D50 = 0.3 um, and an iron-rich lithium manganese iron phosphate slurry is obtained;
[0034] (3) The manganese-rich lithium manganese iron phosphate slurry obtained in step (1) is mixed with the iron-rich lithium manganese iron phosphate slurry obtained in step (2) at a mass ratio of (manganese-rich lithium manganese iron phosphate: theoretically generated iron-rich lithium manganese iron phosphate = 7:3), 12% of the mass of the manganese-rich lithium manganese iron phosphate material is added to glucose, and the mixture is stirred uniformly to obtain a precursor solution;
[0035] (4) The suspension is subjected to spray drying to obtain a precursor, the inlet air temperature of the spray drying is 280 DEG C, and the outlet air temperature is 100 DEG C;
[0036] (5) The precursor is sent into a high-temperature furnace, calcined at 740 DEG C for 10 h under a nitrogen atmosphere, taken out after cooling, and a lithium manganese iron phosphate positive electrode material is obtained;
[0037] Example 3
[0038] The preparation method of the lithium manganese iron phosphate positive electrode material provided by the application comprises the following steps:
[0039] (1) Preparation of manganese-rich lithium manganese iron phosphate slurry: manganese-rich lithium manganese iron phosphate is mixed with pure water, and sand grinding is performed until D50=0.8 um, to obtain manganese-rich lithium manganese iron phosphate slurry, wherein the molar ratio of manganese to iron is n(Mn) / n(Fe)=1.5;
[0040] (2) Preparation of iron-rich lithium manganese iron phosphate slurry: manganese acetate, ferrous acetate, lithium carbonate, and phosphoric acid are added to pure water according to Li / P=1.01, Mn / Fe=0.67, (Mn+Fe) / P=0.965, and stirring and dispersion are performed until uniform, and sand grinding is performed until D50=0.4 um, to obtain iron-rich lithium manganese iron phosphate slurry;
[0041] (3) The manganese-rich lithium manganese iron phosphate slurry obtained in step (1) is mixed with the iron-rich lithium manganese iron phosphate slurry obtained in step (2) according to a mass ratio of (manganese-rich lithium manganese iron phosphate: theoretically generated iron-rich lithium manganese iron phosphate=8:2), and 12% of the mass of the manganese-rich lithium manganese iron phosphate material is added with glucose, and stirring is performed until uniform, to obtain a precursor solution;
[0042] (4) The precursor solution is subjected to spray drying, to obtain a precursor, and the inlet air temperature of the spray drying is 280℃, and the outlet air temperature is 100℃;
[0043] (5) The precursor is sent into a high-temperature furnace, and calcination is performed at 740℃ for 10h under a nitrogen atmosphere, and the lithium manganese iron phosphate positive electrode material is obtained after cooling and taking out;
[0044] Example 4
[0045] The preparation method of the lithium manganese iron phosphate positive electrode material provided by the application comprises the following steps:
[0046] (1) Preparation of manganese-rich lithium manganese iron phosphate slurry: manganese-rich lithium manganese iron phosphate is mixed with pure water, and sand grinding is performed until D50=1 um, to obtain manganese-rich lithium manganese iron phosphate slurry, wherein the molar ratio of manganese to iron is n(Mn) / n(Fe)=1;
[0047] (2) Preparation of iron-rich lithium manganese iron phosphate slurry: manganese acetate, ferrous acetate, lithium carbonate, and phosphoric acid are added to pure water according to Li / P=1.005, Mn / Fe=0.67, (Mn+Fe) / P=0.965, and stirring and dispersion are performed until uniform, and sand grinding is performed until D50=0.5 um, to obtain iron-rich lithium manganese iron phosphate slurry;
[0048] (3) The manganese-rich lithium manganese iron phosphate slurry obtained in step (1) is mixed with the iron-rich lithium manganese iron phosphate slurry obtained in step (2) according to a mass ratio of (manganese-rich lithium manganese iron phosphate: theoretically generated iron-rich lithium manganese iron phosphate=9:1), and 12% of the mass of the manganese-rich lithium manganese iron phosphate material is added with glucose, and stirring is performed until uniform, to obtain a precursor solution;
[0049] (4) spray drying the precursor solution to obtain a precursor, the inlet air temperature of the spray drying being 280°C, and the outlet air temperature being 100°C;
[0050] (5) sending the precursor into a high-temperature furnace, calcining the precursor at 740°C for 10h under a nitrogen atmosphere, and taking out the precursor after cooling to obtain a lithium manganese iron phosphate positive electrode material;
[0051] Examples 5-6
[0052] Compared with Example 3, the slurry sanding D50 of the manganese-rich lithium manganese iron phosphate of Example 5 is 0.6um, and the slurry sanding D50 of the manganese-rich lithium manganese iron phosphate of Example 6 is 1um.
[0053] Examples 7-8
[0054] Compared with Example 3, the slurry sanding D50 of the iron-rich lithium manganese iron phosphate of Example 7 is 0.3um, and the slurry sanding D50 of the iron-rich lithium manganese iron phosphate of Example 8 is 0.2um.
[0055] Examples 9-10
[0056] Compared with Example 3, the mixing mass ratio of the manganese-rich lithium manganese iron phosphate to the theoretically generated iron-rich lithium manganese iron phosphate in step (3) is 7:3 in Example 9, and 6:4 in Example 10.
[0057] Comparative Example 1
[0058] Compared with Example (3), only carbon coating is performed, and the process specifically comprises the following steps:
[0059] (1) mixing the manganese-rich lithium manganese iron phosphate with pure water, adding 12% of the mass of the manganese-rich lithium manganese iron phosphate material of glucose, and sanding to D50=0.8um to obtain a manganese-rich lithium manganese iron phosphate slurry, wherein the molar ratio of manganese to iron is n(Mn) / n(Fe)=1.5;
[0060] (2) spray drying the manganese-rich lithium manganese iron phosphate slurry to obtain a precursor; the inlet air temperature is 280°C, and the outlet air temperature is 100°C;
[0061] (3) sending the precursor into a high-temperature furnace, calcining the precursor at 780°C for 10h under a nitrogen atmosphere, and taking out the precursor after cooling to obtain a lithium manganese iron phosphate positive electrode material.
[0062] Comparative Example 2
[0063] Compared with Example 3, the selected raw materials of the iron-rich manganese iron phosphate slurry are all insoluble in water, and the preparation of the iron-rich manganese iron phosphate slurry specifically comprises the following steps: manganese carbonate, iron phosphate, lithium carbonate, and phosphoric acid are added to pure water according to Li / P = 1.005, Mn / Fe = 0.67, and (Mn+Fe) / P = 0.965, and then stirred and dispersed uniformly, sand-milled to D50 = 0.4 um, and discharged to obtain the iron-rich manganese iron phosphate slurry.
[0064] Comparative Example 3
[0065] Compared with Example 3, the selected raw materials of the iron-rich manganese iron phosphate slurry are all soluble in water, and the preparation of the iron-rich manganese iron phosphate slurry specifically comprises the following steps: manganese citrate, ammonium iron citrate, lithium nitrate, and phosphoric acid are added to pure water according to Li / P = 1.005, Mn / Fe = 0.67, and (Mn+Fe) / P = 0.965, and then stirred and dispersed uniformly, sand-milled to D50 = 0.4 um, and discharged to obtain the iron-rich manganese iron phosphate slurry.
[0066] The manganese iron phosphate positive electrode materials obtained in Examples 1-10 and Comparative Examples 1-3 above were prepared into button cells by the following method and subjected to electrochemical performance evaluation:
[0067] The manganese iron phosphate positive electrode material, Super P (conductive carbon black), and PVDF were uniformly mixed in an NMP solution at a ratio of 8:1:1 to obtain a mixed slurry, the slurry was coated on a bright aluminum foil by hand coating, and then dried at 100°C, after the NMP was completely volatilized, the electrode sheet was punched into an electrode sheet with a diameter of 13 mm, and then the electrode sheet was placed in a vacuum oven and dried at 105°C overnight, after weighing the electrode sheet, it was quickly transferred to a glove box, lithium metal was used as the counter electrode, Celgard 2400 was used as the separator, and the electrolyte was 1 mol / L LiPF6 dissolved in a mixed solvent of EC / DMC / EMC (volume ratio of 1:1:1), and then the assembled battery was tested. The electrochemical performance was tested by a new Wei test system, and the test method of constant current-constant voltage charging (CC-CV) and constant current discharging (DC) was used to test and analyze the charge-discharge behavior of the button cell, and the test voltage range was 2.0-4.35V, and the test results are shown in Table 1.
[0068] Manganese dissolution test: The battery samples of Examples 1-10 and Comparative Examples 1-3 were first fully charged at 0.1C rate, then stored in a 60°C oven for 14 days, then all the batteries were naturally cooled and disassembled, the negative electrode of the sample was digested with 0.1 mol / L aqua regia solution, the content of manganese ions in each sample was tested by ICP, and the manganese content was the dissolved manganese, then the ratio of the mass of the dissolved manganese to the total mass of the active material manganese iron phosphate in the corresponding positive electrode sheet was taken as the degree of manganese dissolution, and the test results are shown in Table 1.
[0069] As can be seen from the data in Table 1, by controlling the particle size, core and outer layer ratio, the compaction density of the lithium manganese iron phosphate positive electrode material can be increased. Compared with the comparative example 1 with only carbon coating, the compaction density is 2.26 g / cm 3 and the compaction density of the comparative example 3 without size particle grading is 2.27 g / cm 3 The compaction densities of examples 1-10 are all increased to 2.34-2.5 g / cm 3 . The comparative example 1 only has limited protection effect on manganese phase by carbon coating, higher manganese dissolution, and lack of grading, the compaction is low. The raw materials selected for the iron-rich slurry in the comparative example 3 are all soluble in water, lack of second nucleation sites, and cannot form size particle grading, so the compaction cannot be improved. The raw materials selected for the iron-rich slurry in the comparative example 2 are all insoluble in water, all the raw materials are in solid state, and cannot form iron-rich layer coating effect, so the manganese dissolution is high, but due to the introduction of iron-rich particles, the overall manganese content is reduced, and the manganese dissolution is improved compared with the comparative example 1.
[0070] Table 1 test data of materials of examples 1-3 and comparative example 1
[0071]
[0072] The test results of examples 1-4 and comparative examples 1 and 3 show that the core-shell structure with concentration gradient has a positive gain on the long-term stability of lithium manganese iron phosphate, and high manganese content is the key to obtain higher energy density: the manganese content of the iron-rich coating layer is relatively low, which successfully reduces the manganese dissolution and the harm caused by it, and the capacity retention rate after long cycle is improved, the difference in manganese and iron content between the inner and outer layers is reduced to avoid lattice mismatch caused by large composition difference, and the long-term stability of the inner and outer layers is improved, which is specifically manifested as the improvement of capacity retention rate after long cycle. The benefits are negatively correlated with the difference in manganese and iron content between the inner and outer layers. The higher the energy density, the higher the manganese content, but the manganese content is also an important reason for manganese dissolution, the higher the manganese content, the greater the probability of dissolution during cycling. Compared with example 1-4, as the manganese content in the manganese-rich core layer decreases and the manganese content in the iron-rich shell layer increases, the manganese and iron ratio of the manganese-rich main core is 1.5, and the manganese and iron ratio of the iron-rich shell layer is 0.67, the comprehensive indexes are more excellent.
[0073] As can be seen from the data of example 1-4, the size of manganese-rich particles also plays a key role in the compaction density and capacity. As the size of manganese-rich particles increases, the compaction density also increases, and the compaction density of example 4 reaches 2.5 g / cm 3 , while the capacity and particle size have an opposite trend, and the 0.1C discharge capacity and energy density of examples 1-4 decrease with the increase of manganese-rich particles. This is because the ionic conductivity of lithium manganese iron phosphate is poor, and the increase of particle size is not conducive to the diffusion of lithium ions, which leads to the difficulty in capacity development. The test results of examples 3, 5 and 6 also have the same trend.
[0074] Comparative Examples 3, 7 and 8, the influence of the particle size of the iron-rich slurry on the performance of the sample, the main influence is the change of the compaction density, the compaction density of the sample is increased after reducing the particle size of Example 7 compared with Example 3, because the small particles in the sample are smaller, which can better fill the voids between large particles, improve the space utilization, and thus improve the compaction density; but as shown in Example 8, compared with Example 3, the small particles are too small to cause agglomeration (red box), so that the gradation effect is poor and the compaction density is reduced. Figure 2
[0075] Comparative Examples 3, 9 and 10, the influence of the mass ratio of the manganese-rich slurry and the iron-rich slurry on the performance of the sample, the increase of the iron-rich slurry in Example 9 compared with Example 3 will lead to the increase of the thickness of the coating layer, so its performance in long cycle and protection of manganese dissolution is more excellent, at the same time, the increase of the proportion of the iron-rich slurry will increase the proportion of small particles, which will be beneficial to the capacity; further increasing the proportion of the iron-rich slurry in Example 10, although it benefits from the increase of small particles to improve the capacity, but due to the too high proportion of small particles, the gradation effect is poor and the compaction density is reduced.
Claims
1. A lithium iron manganese phosphate cathode material, characterized in that, The lithium manganese iron phosphate including large particle core-shell structure and small particle lithium manganese iron phosphate; the large particle core-shell structure lithium manganese iron phosphate includes manganese-rich lithium manganese iron phosphate inner core and iron-rich lithium manganese iron phosphate shell, the manganese content of the inner core is greater than that of the shell, and the iron content of the inner core is less than that of the shell.
2. A method of preparing the lithium iron manganese phosphate cathode material of claim 1, characterized in that, It includes the following steps: (1) Manganese-rich lithium manganese iron phosphate slurry preparation: mixing and grinding manganese-rich lithium manganese iron phosphate with water to obtain manganese-rich lithium manganese iron phosphate slurry; (2) Iron-rich lithium manganese iron phosphate slurry preparation: dissolving thermal decomposition type water-soluble manganese source and iron source into water, then adding non-water-soluble lithium source, phosphorus source and water, and grinding to obtain iron-rich lithium manganese iron phosphate slurry; (3) Mixing the iron-rich lithium manganese iron phosphate slurry obtained in step (2), the manganese-rich lithium manganese iron phosphate slurry obtained in step (1) and a carbon source to obtain a precursor slurry; (4) Spray drying and thermal decomposition: spray drying the precursor slurry to obtain a precursor; (5) Heating and calcining the precursor obtained in step (4) under a protective atmosphere to obtain lithium manganese iron phosphate positive electrode material after cooling.
3. The method for preparing lithium manganese iron phosphate cathode material according to claim 2, characterized in that, In step (1), the manganese-rich lithium manganese iron phosphate, wherein the molar ratio of manganese to iron is n(Mn) / n(Fe)=1-4.
4. The method for preparing lithium manganese iron phosphate cathode material according to claim 2, characterized in that, In step (2), the thermal decomposition type water-soluble manganese source is one or more of manganese nitrate, manganese acetate, manganese citrate, manganese tartrate and manganese ammonium sulfate; the thermal decomposition type water-soluble iron source is one or more of iron nitrate, iron acetate, iron tartrate, ferrous ammonium sulfate, ferric ammonium citrate and ferrous oxalate.
5. The method for preparing lithium manganese iron phosphate cathode material according to claim 4, characterized in that, In step (2), the molar ratio of manganese source to iron source is n(Mn) / n(Fe)=0.25-0.
67.
6. The method for preparing lithium manganese iron phosphate cathode material according to claim 2, characterized in that, In step (3), the manganese-rich lithium manganese iron phosphate and the iron-rich lithium manganese iron phosphate slurry are mixed in a mass ratio of manganese-rich lithium manganese iron phosphate to theoretically generated iron-rich lithium manganese iron phosphate equal to 5-9:1-5; the amount of carbon source added is 8-15% of the total mass of finished lithium manganese iron phosphate.
7. The method for preparing lithium manganese iron phosphate cathode material according to claim 2, characterized in that, In step (1), the particle size range of the manganese-rich lithium manganese iron phosphate slurry is D50=0.3-1um.
8. The method for preparing lithium manganese iron phosphate cathode material according to claim 2, characterized in that, In step (2), the particle size range of the iron-rich lithium manganese iron phosphate slurry is D50=0.1-0.6um.
9. The method for preparing lithium manganese iron phosphate cathode material according to claim 2, characterized in that, In step (4), the inlet air temperature of spray drying is 180-320℃, and the outlet air temperature is 85-115℃.
10. The method for preparing lithium manganese iron phosphate cathode material according to claim 2, characterized in that, In step (3), the carbon source is one or more of glucose, sucrose, starch, cellulose, polyvinyl alcohol, soluble starch, cellulose, ascorbic acid or phenolic resin.
Citation Information
Patent Citations
A core-shell structured nanocomposite material of lithium manganese iron phosphate, its preparation method and application
CN105990562B
Lithium manganese iron phosphate positive electrode material with core-shell structure
CN120089701A
Cited By
A lithium iron manganese phosphate positive electrode material, a preparation method and application thereof
CN122393289A